PELATIHAN PENYUSUNAN RENCANA ANGGARAN BIAYA (RAB) PEKERJAAN JALAN ASPAL DI DESA GAMBUHAN (Universitas Wijayakusuma Purwokerto, 2023)
Regional infrastructure, especially in rural areas, is currently getting more attention from the government. This is evidenced by the existence of village funds prepared by the government to improve village infrastructure. The existence of village funds sourced from the Regional Expenditure Revenue Budget requires village officials to be able to manage the budget in an accountable and transparent manner based on developments in information system technology. One of the activities that can be proposed is the development or maintenance of village infrastructure, which starts with planning activities. However, there are still many village officials who have not mastered this planning, namely in preparing a Budget Plan (RAB) by applicable quality standards. Based on this, through this community service activity in the form of training for Gambuhan Village officials regarding the steps for preparing the RAB, both determining the amount/volume of each planned activity and unit prices by applicable standards and regulations. RAB preparation material was provided regarding asphalt road work. Because in Gambuhan Village, there are still many road conditions that are not good and require periodic maintenance activities, so additional education is needed for village officials regarding good road maintenance methods according to standards. This activity was carried out by all Gambuhan Village officials. After this community service activity was held, it had a positive impact on increasing self-competence, especially in preparing the RAB for Gambuhan Village officials, so that in the future there would be no obstacles in preparing accountability reports.